Struktura aktywów a poziom ich rentowności w gospodarstwach rodzinnych - Bereżnicka, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The article analyzes the structure and return on assets (ROA) in both static and dynamic way in family farms. Basing on the two groups of farms, it was stated that the structure diversified the assets owned. The study showed that the internal structure of the assets in separate groups was similar. However, the farms which showed lower immobility estate reached a higher level of return on assets. But it was a lower value of assets, because a group with higher level of immobilization made a better financial results.